FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK KENDARAAN BERMOTOR DI KANTOR SAMSAT MANADO - Ni Made Aryasusanti; Hendrik Gamaliel; Christian V. Datu (Universitas Sam Ratulangi, 2022)
Abstract: In Indonesia, tax revenue is the primary source of revenue for the government. As a result, one of the most important variables in increasing governmental revenue is taxation. The motor vehicle tax is one sort of local tax (PKB). The goal of this study is to see if a motorized vehicle taxpayer's comprehension of taxation and the tax penalties he or she faces at the Manado SAMSAT office affects their compliance. Quantitative research is the term for this type of study. The sample was chosen by accident, with questionnaires being distributed to 100 two-wheeled motorized vehicle taxpayers who paid their taxes at the Manado SAMSAT office. Multiple linear regression analysis with SPSS 24 was utilized as the analytical strategy. The findings of this study show that motorized vehicle taxpayers at the Manado SAMSAT office have a good and significant effect on their compliance due to their varying comprehension of taxation and tax punishments. This demonstrates that the greater a taxpayer's grasp of taxation and tax penalties, the more likely they are to comply.